PEMANFAATAN STRATEGI TRAP DALAM PEMBELAJARAN LITERASI MEMBACA BAHASA INDONESIA DI MADRASAH TSANAWIYAH - Dwi Ainur Rosyidah; Nur Hasana; Bella Intan Pratiwi; Hemas Haryas Harja Susetya (Jurnal Bastra (Bahasa dan Sastra), 2026)
One important aspect that is the focus of education today is strengthening learners’ literacy. This research aims to contribute to the development of effective literacy learning strategies in the Madrasah Tsanawiyah environment. The study employed a descriptive qualitative method with data collected through interviews, observation, and documentation. The participants consisted of the deputy head of student affairs, an Indonesian language tutor, and grade VIII students of Madrasah Tsanawiyah Zainul Hasan Genggong. Data were analyzed using the Miles & Huberman model. The findings indicate that the TRAP strategy fosters students’ engagement in reading comprehension and summarizing texts in their own words. Its success is influenced by teacher guidance and the availability of suitable reading materials. Challenges identified include limited reading resources and low writing proficiency among some students. Theoretically, this study reinforces the role of interactive strategies in literacy development, while practically, the TRAP strategy can be adapted in secondary school literacy policies to enhance students’ reading and writing skills.